2015
DOI: 10.1182/blood-2014-04-568949
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of mouse hematopoietic stem cells ex vivo by reprogramming cellular metabolism

Abstract: • Treatment with alexidine dihydrochloride, a Ptpmt1 inhibitor, reprograms cellular metabolism and preserves long-term stem cells ex vivo.• Inhibition of mitochondrial metabolism by metformin also decreases differentiation and helps maintain stem cells in culture.The difficulty in maintaining the reconstituting capabilities of hematopoietic stem cells (HSCs) in culture outside of the bone marrow microenvironment has severely limited their utilization for clinical therapy. This hurdle is largely due to the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 25 publications
1
40
0
Order By: Relevance
“…49 Although metformin is not known to directly interfere with TGF-b signaling, several reports indicate interactions between the LKB1/AMPK pathways and TGF-b. 50 Other mechanisms by which metformin may act to protect FA mice include the following: reducing the activity of mitochondrial complex 1 activity, 14 thus potentially reducing oxidative DNA damage 51,52 ; supporting the expansion of HSCs in vitro by switching the metabolic balance between oxidative phosphorylation and anaerobic glycolysis 53 ; and downregulating inflammatory pathways, 54 which are thought to contribute to bone marrow failure in FA. 55 Future studies will be needed to determine whether 1 or more of these known mechanisms in addition to aldehyde quenching are responsible for the beneficial effects of metformin in FA.…”
Section: Discussionmentioning
confidence: 99%
“…49 Although metformin is not known to directly interfere with TGF-b signaling, several reports indicate interactions between the LKB1/AMPK pathways and TGF-b. 50 Other mechanisms by which metformin may act to protect FA mice include the following: reducing the activity of mitochondrial complex 1 activity, 14 thus potentially reducing oxidative DNA damage 51,52 ; supporting the expansion of HSCs in vitro by switching the metabolic balance between oxidative phosphorylation and anaerobic glycolysis 53 ; and downregulating inflammatory pathways, 54 which are thought to contribute to bone marrow failure in FA. 55 Future studies will be needed to determine whether 1 or more of these known mechanisms in addition to aldehyde quenching are responsible for the beneficial effects of metformin in FA.…”
Section: Discussionmentioning
confidence: 99%
“…58 Metabolic reprogramming of quiescent cells is necessary to prevent differentiation and this reprogramming occurs through a shift from oxidative phosphorylation to glycolysis. 59,60 Importantly, glycolysis, although less-efficient than mitochondrial oxidation in generating ATP, reduces oxidative stress and generation reactive oxygen species (ROS), both of which drive stem cell differentiation. Indeed, HSCs are particularly well-suited to tolerate oxidative stress through a well-organized antioxidant defense system.…”
Section: Biochemistry Of the Nichementioning
confidence: 99%
“…Activation of AMPK by metformin, an anti-diabetes drug, enhances glycolysis, but also suppresses HSC differentiation and maintains the stemness of these cells. 59,64 By contrast, metformin has been shown to enhance MSC differentiation, also through AMPK, by upregulating the master osteogenic transcription factor RUNX2. 65 Studies from independent laboratories have confirmed that osteogenic differentiation is driven almost exclusively by glycolysis and that GLUT1 is essential to that process.…”
Section: Biochemistry Of the Nichementioning
confidence: 99%
“…Similarly, co-cultures of cord blood CD34 cells with mesenchymal stromal cells led to the expression of CD34 cells by a factor of 30.1, improving the time required for neutrophil engraftment to 15 days, compared to 24 days in recipients who received un-manipulated cord blood CD34 cells [14]. Growing evidence indicates that targeting metabolism and cellular stress for HSC expansion might potentially lead to successful HSC expansion approaches for transplantation therapies in the future [15,16].…”
Section: Introductionmentioning
confidence: 99%